A rationalization of the weak axiom of revealed preference - Victor H. Aguiar; Per Hjertstrand; Roberto Serrano (The University of Western Ontario, Department of Economics, 2022)
Samuelson's (1938) weak (generalized) axiom of revealed preference- WGARP-is a minimal and appealing consistency condition of choice. We offer a rationalization of WGARP in general settings. Our main result is an exact analog of the celebrated Afriat's theorem, but for WGARP. Its ordinal rationalization is in terms of an asymmetric and locally nonsatiated preference function. Its cardinal rationalization uses a coalitional multi- utility (CMU) maxmin representation with a coherency restriction on the coalition structure. Effectively, the CMU representation aggregates piecemeal preferences within the decision maker (multiple rationales without preference reversals that allow for transitivity violations). Basic consumer theory and welfare analysis are also developed. Extensions to the weak axiom of revealed preference-WARP-and choices obeying the law of demand are included.
Keywords: C60; D10; 330; abstract consumer choice; weak axiom of revealed preference; Afriat's theorem; asymmetric preference function; coalitional multi-utility rationalization; welfare analysis